Developing of Decision Support Soil Information Monitoring System by Statistical Analysis - Várallyai, László; Kovács, Béla; Prokisch, József (Acta Agraria Kaposváriensis, 2004)
The Soil Information Monitoring System (SIM) covers the whole country, and provides the opportunity to create similar information systems for natural resources (atmosphere, supply of water, flora and biological resources etc.). The aim is to relate these databases. The SIM territorial measuring grid consists of 1236 measuring points. These points are representatives. Distribution of the points by soil types represents the variety of soil types in the country. In consequence of accession to the EU, the particular and objective survey of current soil conditions is a very important question, which could be the beginning of the implementation of the modern agrarian environmental management programme. This survey is not much use if the change in condition cannot be investigated continuously at systematic intervals. On the basis of the above mentioned point of view a decision was made to create the planned National Environmental Protection Information and Monitoring System. The first working subsystem was realized as the Soil Information Monitoring System (SIM) module. On a statistically based developed system can be a suitable information system for the management determining the element concentrations precisely. To determine the concentration of the elements, we need only the GPS co-ordinates of the place. The aim is to create an information system of the abovementioned statistical analyses of the submitted samples. The data can be access by a suitable authority system. The supervisor can insert, delete and modify data, the individual user can make queries from the database by SQL technology. The individual users will only need an Internet Browser programme to see the data and create queries.
Keywords: EU accession; Soil Information Monitoring System (SIM); Database on the Internet; Statistical analyse; Decision support